A clínica do não-acontecido e os encontros possíveis em análise - Mello, Camila Rennhard Bandeira de (2024)
From the care of a patient, I was inspired to reflect on the effects of environmental failures on the constitution of the psyche. The uniqueness of this patient prompted me to think about other patients who, like her, present a very fragile sense of self. Over time, I realized that environmental failures, constituting cumulative microtraumas, can impair or even interrupt the process of maturation and, consequently, the formation of the self. The environmental failures I refer to fall under what I term, in this work, as the "non-occurred," emphasizing the lack of encounter between mother and baby in early life, whether due to excesses or deficiencies. This work presents Winnicott's ideas on the functioning of borderline patients and the most suitable treatment for them, considering that the traditional approach, based on free association and interpretation, has limitations in these cases. I start from the premise here of the need to build new intervention strategies in the standard setting to access the psychic life of borderline patients. Building upon Winnicott's concept of the good enough mother and its impact on the constitution of the psyche, this study aims to address the role of the analyst in treating borderline patients. To do so, some anti-traumatic functions of the primary object will be discussed and related to certain functions of the analyst in a context of regression to dependence, aiming to resume psychic processes linked to symbolization and health. To illustrate these points, clinical vignettes from a treated and concluded case will be used. This research is linked to the project "Challenges in mental health: sustainability and subjectivity in the contemporary world," CNPq Call 02/2021, with the objective of analyzing the possibilities of subjective sustenance in the face of contemporary world challenges